Criterios de selección para un agente material de separación en un proceso de deshidratación de etanol por destilación extractiva (2018)
The unconventional separation processes are implemented in the industries for the commercialization of certain products. During the last years, interest in renewable fuel sources has increased, due to environmental concerns regarding the emission of polluting gases generated in the burning of fossil fuels. Currently, the dehydration of ethanol for fuel purposes is one of the most industrially used processes, since ethanol is a compound with a lot of demand in the market due to its physicochemical properties and because it is a compound from renewable biological raw material, promising sustainability environmental and economic. The extractive distillation with solvent is commercially used for the production of anhydrous ethanol; starting from an ethanol-water azeotropic mixture, in which the solvent causes the separation of the azeotropic mixture to be carried out in a distillation column. For this reason, certain selection criteria must be taken into account in order to choose the suitable separation material for the mixture to be separated, which in this case is the ethanol-water mixture. This article presents the criteria that must be taken into account when selecting a separation material agent or entrainer for a specified mixture; it is also presented here by means of a selection matrix, in which some of the selection criteria will be taken into account, a possible material separating agent for the ethanol-water mixture.